Meaningfulness experienced in performing domestic labor in Chinese families: a qualitative study from caregivers’ perspectives - Bo Zhang; Gily Coene (The Journal of Chinese Sociology, 2024)
Abstract The intricately connected interactions among personal choices, traditional cultural ideologies, and modern societal backgrounds have provoked dynamic interpretations and practices in performing domestic labor. The value of domestic labor in terms of macro considerations, such as reproductive value, economic value, and caring value, has been established in scholarly discussions. In China, the emphasis is on the meaningfulness of domestic care for the whole society. However, it remains unclear how family members in contemporary Chinese society understand the meaningfulness of performing domestic labor. This study aims to investigate what kinds of meaning that individuals derive from their day-to-day domestic labor and how the different types of meaningfulness affect their future behaviors in sharing domestic responsibilities. Meaningfulness is a complex notion, but Baumeister’s theory of meaning provides a theoretical framework to understand why humans need meaningfulness in life, the forms that meaningfulness takes, where meaningfulness resides, and how perceptions of meaningfulness are shaped. In total, 48 respondents participated in semi-structured, in-depth interviews concerning their attitudes toward the value of domestic labor. Findings based on in-depth interview data show that the meaningfulness of domestic labor consists of participants realizing their need for belonging, self-efficacy, and a sense of living a good life. These results also suggest that the values of domestic labor illustrated in previous studies, in which domestic labor was conceptualized as reproductive labor, economic activity, and care labor, have little effect on individuals’ lives. Nevertheless, the meaningfulness that individuals experience in daily life continues to motivate their devotion to domestic labor. Finally, the discursive mechanism shaping the meaningfulness of domestic labor is also discussed.